2006
DOI: 10.1177/039463200601900301
|View full text |Cite
|
Sign up to set email alerts
|

Adult Mesenchymal Stem Cells in Dental Research: A New Approach for Tissue Engineering

Abstract: Many adult tissues contain a population of stem cells that have the ability to regenerate after trauma, disease or aging. Recently, there has been great interest in mesenchymal stem cells and their roles in maintaining the physiological structure of tissues. The studies on stem cells are thought to be very important and, in fact, it has been shown that this cell population can be expanded ex vivo to regenerate tissues not only of the mesenchymal lineage, such as intervertebral disc cartilage, bone and tooth-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 67 publications
1
20
0
2
Order By: Relevance
“…The cytofluorimetric analysis excludes any presence of hematopoietic progenitors cells in the primary undifferentiated culture. The negative hematopoietic marker CD34, was in accordance with previous findings 10) for culture of cells derived from human periodontal ligament. Furthermore, our cytofluorimetric analysis confirmed that the cells were positive for the mesenchymal marker …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cytofluorimetric analysis excludes any presence of hematopoietic progenitors cells in the primary undifferentiated culture. The negative hematopoietic marker CD34, was in accordance with previous findings 10) for culture of cells derived from human periodontal ligament. Furthermore, our cytofluorimetric analysis confirmed that the cells were positive for the mesenchymal marker …”
Section: Discussionsupporting
confidence: 90%
“…They are also involved in the mineralization process exerting a key role in bone regeneration techniques. [9][10][11] Osteoblasts can be obtained by isolating and culturing undifferentiated mesenchymal stem cells from embriogenic [12][13][14] or post-natal tissues. 15) The first are considered to be pluripotent cells, 16,17) able to differentiate, in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…and bone marrow stromal cells also known as MSCs which have the capacity to differentiate into connective tissue cells (Pittenger et al, 1999) (see Figure 4). These connective tissues include bone (Arinzeh, 2005;Hong et al, 2006;Noel et al, 2002), fat (Barry and Murphy, 2004;Helder et al, 2007), cartilage (Barry and Murphy, 2004;Caplan, 2007;Noel et al, 2002), intervertebral disc (Richardson et al, 2007;Trubiani et al, 2005;Trubiani et al, 2006), ligament (Sonoyama et al, 2006;Trubiani et al, 2005;Trubiani et al, 2006) and muscle (Barry and Murphy, 2004). Evidence suggests that these cells are also capable of differentiation along myogenic and neurogenic lineages, although these pathways are not normally utilised to demonstrate multipotentiality of isolated MSCs.…”
Section: Identification and Application Of Adult Stem Cellsmentioning
confidence: 99%
“…It was recently found that depletion of NK cells from mice using the anti-asialo GM1 antibody did not affect survival when a low dose (1 x 10 4 ) of T. cruzi trypomastigotes was used for infection; however, when a higher dose was used (5 x 10 5 ), NK-depleted mice had compromised survival compared with C57BL/6 mice (18)(19)(20)(21)(22)(23)(24)(25). Also in vivo and in vitro studies have shown that IL-12-stimulated NK cells can control parasitemia by IFN-γ secretion in the first days of infection with T. cruzi (26)(27)(28)(29).…”
Section: Nk Cells and Parasitesmentioning
confidence: 99%